Metaphors in Pakistani Politics: An Analysis of Imran Khan’s Speeches in General-Election 2018 (Khairulummah, 2023)
AbstractPolitical discourse is abstract and different from daily discourse, therefore; it is difficult for common people to understand. Political leaders use metaphorical language in order to manipulate public instead of making the concept easier for them in terms of General-Election. The study aims to analyze the persuasive strategies of Imran Khan's political speeches that is particularly in the year 2018 in the months of April to July.  The research article uses Conceptual Metaphor Theory (CMT) as theoretical framework to evaluate and interpret public speeches of Imran Khan, conveyed in the year 2018 before the General-Election. Pakistan Tehreek-e-Insaf (PTI) seemed as one of the strongest party in 2018 General-Election of Pakistan. The present study deals with three metaphors; Journey metaphor, War metaphor and Game (Cricket) metaphor, which are frequently used by Imran Khan in his 2018 election speeches to influence the public. We can see the entailment effect of the metaphors he used for he was successful in persuading citizenry to vote him and was elected as 22nd Prime Minster of Islamic republic of Pakistan. The study will help the ordinary people to know the influencing strategies of metaphors used by one of the Pakistani politicians and also will help the scholars to comprehend the collections of metaphor used by Pakistani political leaders in times of elections.